The Design of the SBMPTN Tryout System on the Official Website of the Tutoring Institute “Road to PTN” - Lalu Ryan Ravisafitra; Rina Dewi Indahsari (Procedia of Engineering and Life Science, 2021)
The design of the Road to PTN Tutoring Institution official website serves to assist students in preparing for the SBMPTN, as well as complete information from Road to PTN’s social media; LINE, Instagram, Youtube and Twitter. On the website that is built there are several main features, those are simulation, a user can buy a tryout class by filling up the balance (top up) using a bank ATM, the user can also download the test results, see the rank results, and get the results of the talent interest analysis. Several predictions of campus rank and department are displayed in the premium tryout class including the leaderboard rank profile (top 10). Beside that there is information on the article menu which contains tips and motivation. Issues published are made via the admin dashboard including confirmation of user activity. In the tests carried out on the Road To PTN official website, users can use all the available features including, login, create an account, set up accounts, fill in balances, withdraw balances, perform simulations, view rank results, download test results and create articles or read articles. And the admin has been able to process the data on the website. This is evidenced by the results of user testing functional testing and admin functional testing which results in all features being successfully used as expected.